Preparation of a novel Ce and Sb co-doped SnO2 nanoflowers electrode by a two-step (hydrothermal and thermal decomposition) method for organic pollutants electrochemical degradation. (10th April 2022) - Man, Shuaishuai; Zeng, Xuzhong; Yin, Zehao; Yang, Haifeng; Bao, Hebin; Xu, Ke; Wang, Li; Ge, Xiaotian; Mo, Zhihong; Yang, Wenjing; Li, Xueming
Highlight: A novel Ce and Sb co-doped SnO2 nanoflowers electrode was prepared by a two-step (hydrothermal and thermal decomposition) method. The Ti/Ce-Sb-SnO2 NFs electrode achieved nearly 100% methylene blue removal efficiency within 90 min. The electrochemical stability of the anode was prolonged from 8.2 h to 15.5 h after the introduction of Ce. Abstract: Nanostructured Sb-SnO2 electrodes with high electrochemical activity and stability are urgently desired for electrochemical oxidation of refractory organics in wastewater treatment, yet hard to be controlled and synthesized. Hence, we combined the hydrothermal method and thermal decomposition technologies to prepare a novel Ce and Sb co-doped SnO2 nanoflowers electrode (Ti/Ce-Sb-SnO2 NFs). The incorporation of Ce endowed the Ti/Ce-Sb-SnO2 NFs anode with an increased oxygen evolution over-potential (OEP) (1.99 V vs . SCE), lower charge transfer resistance (7.54 Ω⋅cm 2 ), large specific electrochemical active surface area (141.83), a great number of active sites and superior OH generation ability. Consequently, nearly 100% decolorization efficiency and 91.45% chemical oxygen demand (COD) mineralization efficiency of methylene blue (MB) (20 mg/L) were achieved by the Ti/Ce-Sb-SnO2 NFs anode within 90 min. Additionally, the Ti/Ce-Sb-SnO2 NFs anode stability was also improved with a longer accelerated lifetime (15.5 h) than the given Ti/Sb-SnO2 NFs electrode (8.2 h). We also prepared other nanostructured (nanoparticles, nanoclusters and nanosheets) Sb-SnO2 electrodes with high oxidation capacity utilizing this two-step method, which demonstrated its great versatility. Accordingly, this work could provide a new strategy for fabricating efficient and stable rare earth elements (Ce, Nd, La, etc.) and Sb co-doped SnO2 nanostructured electrodes for decomposition organic pollutants in the field of wastewater treatment. Graphical abstract: Image, graphical abstract